(untitled) (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
The Banggai cardinalfish (Pterapogon kauderni Koumans, 1933) is a conservation priority species in Indonesia. To date there has been no effort to rear Banggai cardinalfish on a commercial scale, so that fish are still mainly captured from the wild. Therefore, efforts are being made to develop ex-situ Banggai cardinalfish culture using different types of natural feed. This research aimed to determine the best type of natural feed to promote the growth and survival of juvenile Banggai cardinalfish. The research was conducted during December 2021-January 2022, at the Central Sulawesi Provincial Marine Affairs and Fisheries Service Hatchery, in Mamboro Village, Palu City. The study used 3 treatments with 6 replicates each: A (Artemia), B (Cullex), and C (Tubifex). The use of different natural feeds had a significant effect on net weight gain but did not have a significant effect on daily growth rate and net growth in length. Treatment B (Cullex) gave the highest net weight gain and daily growth rate of 0.08 ± 0.3 g and 0.25 ± 0.1 % respectively; treatment A (Artemia) gave the highest net growth in length of 0.5 ± 0.2; and survival rate was highest (100%) under treatment B (Cullex).